Authors, Audiences, and Old English Verse - Bredehoft, Thomas A. (Book collections on Project MUSE., 2009)
Authors, Audiences, and Old English Verse re-examines the Anglo-Saxon poetic tradition from the eighth to the eleventh centuries and reconsiders the significance of formulaic parallels and the nature of poetic authorship in Old English.